A simplified prediction method for evaluating tunnel displacement induced by laterally adjacent excavations. (March 2018) - Zheng, Gang; Yang, Xinyu; Zhou, Haizuo; Du, Yiming; Sun, Jiayu; Yu, Xiaoxuan
Abstract: This investigation aimed to develop a simplified semi-empirical method of assessing the deformation of tunnels laterally adjacent to excavations. A finite element analysis using the hardening soil model with small-strain stiffness (HSS model) was performed to study the influence of the excavation depth, the horizontal displacements of retaining structures, and the relative tunnel locations on the responses of existing tunnels. A simplified model was developed based on the numerical results, and a database comprising 14 case histories was collected. Comparisons were made with the generated artificial data and the collected case histories to demonstrate the accuracy of the proposed model.